Inhibition of 7-dehydrocholesterol reductase prevents hepatic ferroptosis under an active state of sterol synthesis - Yamada, Naoya; Karasawa, Tadayoshi; Ito, Junya; Yamamuro, Daisuke; Morimoto, Kazushi; Nakamura, Toshitaka; Komada, Takanori; Baatarjav, Chintogtokh; Saimoto, Yuma; Jinnouchi, Yuka; Watanabe, Kazuhisa; Miura, Kouichi; et al. (Nature communications, 2024)
Recent evidence indicates ferroptosis is implicated in the pathophysiology of various liver diseases; however, the organ-specific regulation mechanism is poorly understood. Here, we demonstrate 7-dehydrocholesterol reductase (DHCR7), the terminal enzyme of cholesterol biosynthesis, as a regulator of ferroptosis in hepatocytes. Genetic and pharmacological inhibition (with AY9944) of DHCR7 suppress ferroptosis in human hepatocellular carcinoma Huh-7 cells. DHCR7 inhibition increases its substrate, 7-dehydrocholesterol (7-DHC). Furthermore, exogenous 7-DHC supplementation using hydroxypropyl β-cyclodextrin suppresses ferroptosis. A 7-DHC-derived oxysterol metabolite, 3β,5α-dihydroxycholest-7-en-6-one (DHCEO), is increased by the ferroptosis-inducer RSL-3 in DHCR7 -deficient cells, suggesting that the ferroptosis-suppressive effect of DHCR7 inhibition is associated with the oxidation of 7-DHC. Electron spin resonance analysis reveals that 7-DHC functions as a radical trapping agent, thus protecting cells from ferroptosis. We further show that AY9944 inhibits hepatic ischemia-reperfusion injury, and genetic ablation of Dhcr7 prevents acetaminophen-induced acute liver failure in mice. These findings provide new insights into the regulatory mechanism of liver ferroptosis and suggest a potential therapeutic option for ferroptosis-related liver diseases. Ferroptosis has been connected to liver disease through unclear mechanisms. Here, the authors identify the terminal enzyme of cholesterol synthesis, 7-dehydrocholesterol reductase, as a regulator of ferroptosis in hepatocytes that suppresses ferroptosis through 7-dehydrocholesterol accumulation.